Rancang Bangun Mesin Pencetak Biopelet dari Sekam Padi - Supriandi Monoarfa; Romi Djafar; Syamsu Akuba; Siradjuddin Haluti (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2022)
Energy is one of the most important community needs in supporting everyday life such as cooking. The energy in question can come from fossil fuels or wood. However, its availability will decrease over time, especially fossil fuels. Therefore, it is necessary to have other alternatives as a substitute for fuel. One of the materials that can be used as an energy source is biopellet. This study aims to design a machine used to make biopellets. The biopellet in this study was made from rice husk as raw material. This research was conducted through several stages, namely design and design, manufacture and fabrication, and testing. The biopellet printing machine has a tube-like shape with an outer diameter of 300 mm, whereas on the inside there is a mold with a hole with a diameter of 15 mm. The biopellet printing machine is also equipped with a roller that functions to press the dough to pass through the mold. Tests for making biopellets were carried out three times with different compositions of raw materials. The first test consisted of adhesive and rice husk with a ratio of 0.50:1. The second and third tests have adhesive and rice husk ratios of 0.75:1 and 1:1, respectively. 0.50 liters of water was added to each mixture to form a dough. The test results show that biopellets have different structures and characteristics. The third test had a dense biopellet structure, a smooth and uniform surface, and fewer fractures and cracks. In addition, the productivity is also higher than the first and second tests. This difference is of course many factors that influence, such as emphasis, the main composition of the material, and the size of the main material.